Assessment of the Effects of Sleep Hours and Academic Performance on Psychological Distress in University Students - , Victor Moses, Godwin Augustina (Archives of Current Research International, 2018)
Like in other parts of the world, the extent of psychological distress among young adults in the Nigerian universities is worrisome with over 31.9% likely to have a severe mental disorder. It is a fact that a number of factors contribute to the problem. This article presents the results of a study designed to investigate the effects of sleep hours and academic performance on psychological distress among University students. The correlational research design was used and three hundred and eighty-five students (385 [male=200 and female= 185]) participated in the study. The data collected through questionnaire was analyzed using one-way analyses of variance at p<.05. The analysis was done using JMP version. 13.2. The results revealed significant effects of sleep hours on the psychological distress F (3,381) = 17.750, p<.001, with students sleeping an average of ≤ 4 hrs reporting significant distress level, t = 6.16, p<.001. Academic performance was found to predict psychological distress F (3,381) 381 = 6.864, p<.001, with performance below average predicting psychological distress positively, t = 4.09, p<.001. The study concludes that poor sleep quantity and academic performance below average may significantly predict psychological distress among the study sample. The outcome of this study, therefore, provides psychologists, counsellors and educationist with the necessary information required to enable the development of an intervention that can help to encourage good sleep habit and improved academic performance to reduce psychological distress.